Effect of Physiological Maturity and Germinating Media on Zanzibar Clove Seeds Viability - R Pelealu, Rian Virvian Hidayat; Widajati, Eny; Suwarno, Faiza C. (Buletin Penelitian Tanaman Rempah dan Obat, 2019)
Low seeds quality of the clove tree may attribute to the low national productivity of cloves in Indonesia.  The study aimed to determine the level of physiological fruit maturity and the effect of germination media on the viability of clove seeds. The study was performed at the Leuwikopo Seeds Storage and Quality Testing Laboratory and Leuwikopo Research Installation, Bogor, in October 2017 to December 2018. The material used was the Zanzibar clove seeds from ≥ 10 years old trees. The clove seeds obtained from a farmer’s plantation in Tolitoli District, Central Sulawesi. The study arranged in a split-plot design, with four replications, with the main plot was four levels of seed viability based on fruit colors: reddish-green, pink, red, and dark red. The subplots were three types of germination media, namely sand, cocopeat, and zeolite.  Thus, there were twelve treatments. Each plot consisted of 40 seeds for germination test and five seeds for water content determination. The results showed that the percentage of clove seeds viability negatively influenced by the level of fruit maturity based on the color of the fruit but was affected by the germination media. Good physiological quality of clove seeds characterized by dry seed weight of 2.70  g,  100 %  germination rate, vigor index of 73.75 %, and growth rate of 1.19 % etmal-1. Among the three types of germination media tested (sand, cocopeat, and zeolite), sand was the best germination media for clove seeds. Hence it is recommended to seeds producer.